Peran Branding dan E-Commerce dalam Mempertahankan Eksistensi Kerajinan Anyaman Tasikmalaya - Teten Rohandi; Dyah Nurhayati (Jurusan Seni Rupa ISBI Bandung, 2025)
This study aims to analyze the role of branding and e-commerce in efforts to maintain the existence of woven crafts in Tasikmalaya. Tasikmalaya woven crafts are a local cultural heritage facing significant challenges amid modern market competition and changes in consumer behavior. To overcome these challenges, an adaptive marketing strategy is required, one of which involves integrating strong branding aspects and utilizing digital platforms. The method used in this research is qualitative with a descriptive-analytical approach. Data was collected through in-depth interviews with craft business owners, artisans, and relevant stakeholders, as well as through observation and document study. The collected data was analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the role of branding and e-commerce is highly essential and has a significant impact on maintaining and enhancing the existence of Tasikmalaya woven crafts. Effective branding, which includes visual identity, product narrative (storytelling), and unique values, successfully builds a positive image and increases product competitiveness. Meanwhile, the use of e-commerce opens up wider market access, reaching consumers from various regions, and facilitating efficient transactions. The combination of these two elements not only maintains the sustainability of the woven craft business but also offers the potential for growth and strengthening the image of local products at both national and international levels.